Impact of a home-based nutrition and exercise intervention in improving functional capacity associated with falls among rural seniors in Canada. (10th December 2018) - Johnson, Shanthi; McLeod, Bill; Gupta, Sabyasachi; McLeod, Katherine
Abstract : Purpose: A six-month randomized controlled trial was conducted to examine the impact of a home-based nutrition and exercise intervention on functional capacity to prevent falls among rural seniors. The paper aims to discuss this issue. Design/methodology/approach: Men and women ( n =134), aged 60 and older were assigned to one of four groups: exercise, nutrition, exercise-nutrition and control. Participants in the exercise and exercise-nutrition groups performed a home-based exercise program (Home Support Exercise Program), and the nutrition and exercise-nutrition groups received a liquid nutritional supplement (Ensure®) for six months. Participants were assessed at baseline and six months on functional mobility, balance, flexibility and endurance. Findings: There were significant group differences over time for functional reach and the Timed Up and Go test, with significant differences existing between exercise and nutrition-exercise and exercise and nutrition groups, respectively. Overall, the exercise group out-performed the other groups in terms of functional capacity and psychological well-being. Research limitations/implications: Improvement of functional health among rural seniors is achievable through the delivery of a home-based intervention focusing on exercise and nutrition. Practical implications: The study also shows that the effective delivery of an intervention to successfully address a fundamental and persistent problem is possible using existing resources; however, it requires a commitment of focus and energy over considerable time. Social implications: The approach and findings promotes seniors to age in place in rural context. It shows feasibility of delivering a practical intervention in the rural setting through the health care infrastructure of home care. Originality/value: Apart from the rural context, the study was innovative at many levels. Specifically, this intervention addressed a significant health issue (functional capacity, falls and injuries), involved frail rural seniors (often hard to reach through community-based programs), provided a feasible intervention (multiple component exercise program), used existing infrastructure (e.g. home care), and espoused community development principles (active involvement of community partners, researchers, and trainees). As well, the study had built-in mechanisms for monitoring and support through the involvement of home service workers who received training. This approach created a strong research to practice connection (another innovation) and was critical for the credibility of the investigation, as well as the sustainability of the intervention. Another innovation was the inclusion of a population health perspective as the study framework. From the population health perspective, this research addressed several determinants of health in rural and urban areas that include: physical environment (intervention within people's home and rural context), social environment and social support networks (through existing infrastructures of home support workers), health services (availability of health promotion strategy delivered through the health care system) and personal health practices and coping skills (exercise).